Cognitive Load Disrupts Implicit Theory-of-Mind Processing - Schneider, Dana; Lam, Rebecca; Bayliss, Andrew P.; Dux, Paul E. (Psychological Science, 2012)
Eye movements in Sally-Anne false-belief tasks appear to reflect the ability to implicitly monitor the mental states of other individuals (theory of mind, or ToM). It has recently been proposed that an early-developing, efficient, and automatically operating ToM system subserves this ability. Surprisingly absent from the literature, however, is an empirical test of the influence of domain-general executive processing resources on this implicit ToM system. In the study reported here, a dual-task method was employed to investigate the impact of executive load on eye movements in an implicit Sally-Anne false-belief task. Under no-load conditions, adult participants displayed eye movement behavior consistent with implicit belief processing, whereas evidence for belief processing was absent for participants under cognitive load. These findings indicate that the cognitive system responsible for implicitly tracking beliefs draws at least minimally on executive processing resources. Thus, even the most low-level processing of beliefs appears to reflect a capacity-limited operation.